The influence of work environment and job satisfaction on the performance of BLUD employees at the RSUD Palembang BARI during the COVID-19 pandemic - Asih, Nova Nur; Zunaidah, Zunaidah; Widiyanti, Marlina; Adam, Mohamad (International research journal of management, IT and social sciences, 2022)
This study aimed to determine and analyze the influence of the work environment and job satisfaction on the performance of BLUD employees at the RSUD Palembang BARI during the COVID-19 pandemic. The data used in this study is primary data using a questionnaire as an instrument to measure research variables. Questionnaires were distributed to 114 respondents, employees of BLUD at the RSUD Palembang BARI. The data collected from the questionnaire instrument was processed using the SPSS program to perform multiple linear regression tests. The results showed that the work environment and job satisfaction partially had a positive and significant effect on the performance of BLUD employees at the RSUD Palembang BARI during the COVID-19 pandemic. The results also show that the work environment and job satisfaction have a positive and significant effect on the performance of BLUD employees at the RSUD Palembang BARI during the COVID-19 pandemic.